Evaluation of surface treatments for RC structures failing to meet South African durability index requirements - Burmeister, Nicholas (Department of Civil Engineering, 2015)
In many countries the budget for repairing existing infrastructure already exceeds that of building new infrastructure. The main durability problem is corrosion of reinforcing steel caused by the ingress of aggressive agents and moisture. The South African durability index approach makes use of indices to evaluate the potential durability of concrete. Once limiting values on the as built structure meet specific requirements, the structure is considered to be inherently durable. However, a clear design methodology or guidelines for concrete structures that do not meet the specified minimum requirements needs to be established. The potential for using surface treatments to prevent the ingress of corrosion causing agents (carbon dioxide, chloride ions and moisture) is presented in literature but the extent of protection and durability of these products is largely unknown. A laboratory investigation was developed to evaluate the performance and longevity of surface treatments under accelerated weathering and exposure conditions. Poor quality concrete failing to meet durability requirements was treated with six products and exposed to accelerated weathering conditions. The carbon dioxide and chloride ion resistance was then evaluated to establish performance and durability characteristics for each of the products. Results indicate that surface treatments restrict the passage of deleterious agents and certain products can be used as an acceptable method of corrosion prevention. The pure silane coating was found to effectively reduce the ingress of chlorides while the acrylic dispersion, acrylic resin, cement based and cement based fibre reinforced coatings were effective in preventing carbonation. Furthermore, it was found that the increased service life due to the application of anti - carbonation coatings could be quantified with a specific number of years. Service life quantification due to improved chloride ion resistance was not possible since modified and custom tests differing from the standard bulk diffusion test were used to evaluate performance. Chloride resistance was improved due to the pure silane however service life improvements could not be quantified. Unexpected failures occurred during the laboratory investigation rendering a number of tests inconclusive. Some guidance based on the knowledge gained during this project is provided for future testing.